Performance and Carcass Characteristics of Broilers Fed Five Different Commercial Vitamin-Mineral Premixes in Ibadan, Nigeria - Ogunwole, O.A.; Kolade, E.O.; Taiwo, B.A. (International Journal of Poultry Science, 2012)
The relative efficacy of five proprietary vitamin-mineral premixes on performance and carcass characteristics of broiler chickens was undertaken in a trial lasting six weeks at the Teaching and Research Farm, University of Ibadan, Ibadan, Nigeria. A total of two hundred and eighty eight 1-day broiler chicks of Abor acre strain were randomly allotted to six dietary treatments of forty eight chicks per treatment. Each treatment was a triplicate of sixteen chicks per replicate. Six isocaloric and isonitrogenous diets were formulated. Diet 1 (T1) was the control without any premix. Other diets were supplemented appropriately with 0.25% Daramvita (T2), Biorganics (T3), Hinutrients (T4), Optimix (T5) and DSM Nutripoults (T6). The experimental diets were offered to the respective birds with water given ad libitum. The design of the experiment was a completely randomized design. The feed conversion ratio of birds on T3, T4, T5 and T6 were 2.64, 2.58, 2.61 and 2.57 respectively and were significantly different (p